Assessing the Differences in Measurement of Degree of Spondylolisthesis Between Supine MRI and Erect X-Ray: An Institutional Analysis of 255 Cases. Issue 4 (5th August 2019) - Alvi, Mohammed Ali; Sebai, Adeeb; Yolcu, Yagiz; Wahood, Waseem; Elder, Benjamin D; Kaufmann, Timothy; Bydon, Mohamad
Abstract: BACKGROUND: Degenerative spondylolisthesis is the displacement of one vertebral body over the adjacent one. While standing and flexion-extension X-rays are preferred for determining listhesis, magnetic resonance imaging (MRI) is often utilized to assess the compression of nerve root or spinal cord. OBJECTIVE: To investigate the difference in radiographic measurements of spondylolisthesis between X-rays and MRI. METHODS: We retrospectively reviewed the records and radiographic images of patients with a confirmed diagnosis of spondylolisthesis undergoing operation in 2016. Primary variable of interest was the degree of slippage as per the Meyerding method. Agreement between the 2 reviewers was assessed using the 2-way intraclass correlation coefficient (ICC) for slippage percentage and Cohen's Kappa for grade. Agreement of Meyerding grade between the 2 imaging techniques was assessed using Cohen's Kappa, while the slip percentage measured for each technique was compared using a Bland-Altman (BA) plot, mean difference (MD), and 1-way ICC. RESULTS: A total of 255 cases were analyzed. ICC between the 2 reviewers was found to be 0.75 (95% confidence interval [CI] = 0.64-0.83, P < .001) for X-ray and 0.76 (95% CI = 0.66-0.83, P < .001) for MRI. Agreement between X-ray and MRI for grading of spondylolisthesis was found to be poor (kappa = 0.32, P < .001). BA plot between X-ray and MRI measurements revealed an MD of 4.4% (95% limits of agreement: –10.3% to 19.3%) with 5.16% observations outside the limits of agreement and 1-way ICC of 0.35 showing poor agreement. Conclusion: Our results demonstrate the discrepancy of spondylolisthesis grade measurements between weight-bearing X-ray and nonweight-bearing MRI. Careful evaluation of both imaging technique is warranted to determine the final severity of pathology and tailoring of management plan.